Hantering av gödsel på svenska hästanläggningar - Eriksson, Anna (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
The horse industry in Sweden is a large part of the agricultural activity (Jordbruksverket, 2017). The management of the manure is important because it contains high levels of the three important plant nutrients: nitrogen (N), phosphorus (P) and potassium (K). Manure management in paddocks during the winter months has been shown to be an important factor in reducing eutrophication which is the result of a plentiful supply of N, P and K to the ground. On the website of the Swedish Board of Agriculture, there are provisions for how long the manure must be stored on a horse facility and the quantities of N that can be spread on the fields. The manure should be stored in such a way that the leaching of nutrients into the surrounding environment doesn’t exist. Several studies have shown that horse manure that is stored directly on the ground quickly contribute to a negative impact on soil contents of N and P (Parvage, et al., 2011; Dahlin & Johansson 2008; Airaksinen et al., 2007; Parvage, et al., 2013). If the soil lacks the green cover it is more negatively affected because the nutrients disappear directly into the ground. The surface water from these paddocks are also affecting the surrounding environment as it contains significantly higher levels of N and P. Not only the areas in the paddock where the manure is collected have higher levels of N and P, the same applies to areas where the feeding takes place, and where the horses drink water. The purpose of the completed questionnaire study was to identify how horse manure is handled at facilities around Sweden. The study focuses primarily on the management of the manure produced during the winter months when the horses are staying in their winter paddocks. The storage of manure on the facilities was also examined. The results of this survey study indicated that there is an association between the size of the paddocks and how often the manure is removed. There is also a correlation between how many hours the horses spend in the paddocks and the size of the paddock. The study shows that the manure in most of the smaller paddocks that the horses are kept in during winter are not regularly removed. There is reason to discuss the recommendations of how the manure would be handled on the Swedish horse facilities. On the question about how the manure were stored at the facility two of the requester answered that the manure was stored directly on the ground, which also causes an increased leaching of nutrients to the soil.